2011
DOI: 10.1292/jvms.11-0051
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibilities of Listeria monocytogenes Isolated in Japan

Abstract: ABSTRACT. The antimicrobial susceptibility of 201 Listeria monocytogenes isolates from foods, environments, animals and human patients in Japan was determined. All isolates were susceptible to ampicillin, the first choice of drug for listeriosis treatment, chloramphenicol, dihydrostreptomycin, erythromycin, enrofloxacin, gentamicin, kanamycin, lincomycin, nosiheptide, salinomycin, vancomycin, and virginiamycin. A human strain was resistant to oxytetracycline. The Minimum Inhibitory Concentration (MIC) for 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…In our previous study about the resistance against 16 types of antibiotic in 101 isolates from patients and 100 isolates from foods and environment, we found that only 1 isolate from patient was resistant to oxytetracyclin and tetracyclin (Okada, 2011). This result supports that the listerial resistant rates to antibiotics in Japan are at low level basically.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In our previous study about the resistance against 16 types of antibiotic in 101 isolates from patients and 100 isolates from foods and environment, we found that only 1 isolate from patient was resistant to oxytetracyclin and tetracyclin (Okada, 2011). This result supports that the listerial resistant rates to antibiotics in Japan are at low level basically.…”
Section: Discussionsupporting
confidence: 60%
“…All strains were tested their susceptibilities against 8 types of antibiotics; ampicillin (ABPC; Wako Chemicals, Tokyo, Japan), chloramphenicol (CM; Wako), enrofloxacin (ERFX; Sigma, St. Louis, USA), erythromycin (EM; Sigma), gentamicin (GM; Wako), kanamycin (KM; Wako), penicillin (PN; Wako) and tetracycline (TC; Wako) by standard plate dilution method as in the previous study (Okada, 2011). All antibiotics were used in two-fold serial dilution at concentrations from 0.25 to 128µg/ml.…”
Section: Antibiotics Susceptibility Testmentioning
confidence: 99%
“…Listeria isolates from food, environment, animal and human sources have been found to be resistant to commonly used antibiotics, including gentamicin, cotrimixazole and ofloxacin (Low & Donachie 1997;George 2002;Rahimi et al 2012;Soni et al 2013;Ndahi et al 2014). Since chemotherapy with antibiotics is the only available method for treatment of listeriosis, judicious use of these drugs in medical and veterinary practices along with monitoring of antibiotic susceptibility is very important (Okada et al 2011;Barbosa et al 2013).…”
Section: Veterinary Quarterly 11mentioning
confidence: 99%
“…Most of the time, infection in animals is subclinical but severe forms can also occur (OIE 2014). The disease is characterized by septicaemia, encephalitis, meningitis, meningoencephalitis, rhombencephalitis, abortion, stillbirth, perinatal infections and gastroenteritis (Brugere-Picoux 2008; Barbuddhe & Chakraborty 2009;Okada et al 2011; Barbuddhe et al 2012;Disson & Lecuit 2013;Limmahakhun & Chayakulkeeree 2013;Mateus et al 2013;OIE 2014). The organism has an intracellular life cycle that can pass from cell to cell without release from the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Harakeh et al (14) reported a high percentage of resistance to penicillin, ampicillin, and chlor amphenicol among L. monocytogenes isolates from dairybased food products. Very few studies on antibiotic resistance of L. monocytogenes have been conducted in Japan (32). Antimicrobial agents are used for growth promotion to improve animal husbandry in Japan.…”
Section: Discussionmentioning
confidence: 99%